Social Dynamics of Actors in Muhammadiyah Organization: Exemplary Behavior, Dual Roles, and Ideological Negotiations in Enrekang Regency - Saidang, Saidang; Usman, Arifuddin; Torro, Supriadi; Kamaruddin, Syamsu A. (Darul Yasin Al Sys, 2025)
This research is motivated by the importance of understanding the role of actors in the dynamics of religious organizations, especially Muhammadiyah in Enrekang Regency, which faces social, ideological, and cultural complexity. Muhammadiyah actors at the local level not only carry out structural functions, but also play a cultural role as agents of social change and guardians of social harmony. The purpose of this study is to analyze how exemplary behavior, dual roles, and negotiation strategies of Muhammadiyah actors play a role in responding to the developing social and ideological dynamics. This study uses a descriptive qualitative approach with a case study method, through in-depth interviews, participant observation, and documentation studies. Data were analyzed using thematic and interpretive analysis techniques with reference to Anthony Giddens' structuration theory and Pierre Bourdieu's praxis theory. The results of the study show that Muhammadiyah actors have a strategic role in bridging the ideological values ​​of the organization with the needs of the local community through social exemplars, flexibility of action, and a cultural approach. The discussion shows that the success of the organization is highly dependent on the quality of the actor's agency, not solely on structural strength. This study provides theoretical and practical contributions in understanding the dynamics of community-based religious organizations in complex and pluralistic social spaces.